2014
DOI: 10.1152/jn.00820.2013
|View full text |Cite
|
Sign up to set email alerts
|

Organization of pontine reticulospinal inputs to motoneurons controlling axial and limb muscles in the neonatal mouse

Abstract: Sivertsen MS, Glover JC, Perreault MC. Organization of pontine reticulospinal inputs to motoneurons controlling axial and limb muscles in the neonatal mouse. J Neurophysiol 112: 1628 -1643, 2014. First published June 18, 2014 doi:10.1152/jn.00820.2013.-Using optical recording of synaptically mediated calcium transients and selective spinal lesions, we investigated the pattern of activation of spinal motoneurons (MNs) by the pontine reticulospinal projection in isolated brain stem-spinal cord preparations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
(104 reference statements)
0
17
1
Order By: Relevance
“…In accordance with previous reports (Bretzner and Brownstone, 2013; Kimura et al, 2013), we found V2a neurons to be exclusively glutamatergic. They thus represent a unique contingent that diverges from other excitatory descending systems, thought to favor excitability (Dubuc et al, 2008; Hägglund et al, 2010; Perreault and Glover, 2013; Sivertsen et al, 2014). Importantly, our split-bath experiments in vitro indicate that the V2a descending command is integrated in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous reports (Bretzner and Brownstone, 2013; Kimura et al, 2013), we found V2a neurons to be exclusively glutamatergic. They thus represent a unique contingent that diverges from other excitatory descending systems, thought to favor excitability (Dubuc et al, 2008; Hägglund et al, 2010; Perreault and Glover, 2013; Sivertsen et al, 2014). Importantly, our split-bath experiments in vitro indicate that the V2a descending command is integrated in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have focused here on the pRS neuron populations in the core of the PRF that relate directly to the stimulation sites that we identified in our previous study (Sivertsen et al, ), it is also important to note that descending pathways from the pontine reticular formation and the pons in general are functionally heterogeneous. Several specific pathways to the spinal cord have been identified that regulate such diverse functions as respiration, nociception, micturition, defecation, sexually triggered glandular secretion, and noradrenergic modulation (for review see Holstege and Kuypers, ; Holstege, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo preparations of the neonatal mouse spinal cord are capable of generating fictive locomotor activity and this has facilitated both anatomical and physiological studies of the underlying synaptic connections (Kiehn, ). With the brainstem attached, it is possible to investigate the descending control of spinal motor circuits with great precision (Szokol et al, ; Sivertsen et al, ; Kasumacic et al, ). Because the structures are small and myelination is still nascent, high‐throughput optical methods for physiological investigation are especially feasible (Szokol and Perreault, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice are born at a less mature stage than humans, such that SCI in neonatal mice would correspond to a late third trimester in utero SCI in humans. Although many descending axon tracts have already reached the spinal cord and established synaptic connections onto spinal neurons by birth in the mouse (Auclair et al, 1999;Szokol et al, 2008Szokol et al, , 2011Kasumacic et al, 2010Kasumacic et al, , 2012Kasumacic et al, , 2015Sivertsen et al, 2014), some, including the corticospinal tract, have not, and even those that have may undergo further postnatal maturation (Lambert et al, 2016). Thus, SCI in neonatal mice represents a situation in which both ongoing development and injury recovery mechanisms occur simultaneously.…”
Section: Relevance To Human Spinal Cord Injurymentioning
confidence: 99%